(untitled) (Biological Sciences - PJSIR, 2022)
The ionic conductivity of bromamine- T (BAT) in water and methanol as solvent has been studied as a function of temperature. The conductance data have been analysed by the Debye-Huckel, Fuosskraus, Shedlovsky and Fuoss Accascina Equations. The energy of activation of the rate process, thermodynamic parameters, molar conductivity at infinite dilution (AO ), Walden constant, dissociation and association constants (1<’s) have been calculated. A comparison of the A’:;m and K’s values calculated from various equations has been made. An attempt is also made to propose the BAT as a weak electrolyte under the studied experimental conditions.